Sexual Homicides in China: Exploring the Offender, Victim, and Offense Characteristics - Chan, Heng Choon (International journal of offender therapy and comparative criminology, 2019)
Nearly all information available on sexual homicides are limited to studies conducted in the West. Little is known about sexual homicides that occurred in China. The current study is arguably the first to explore the offender, victim, and offense characteristics of Chinese sexual homicides. Over a period of 23 years (1994 to 2016), the data of 59 cases collected from two data sources (i.e., published Chinese case reports and police data) are examined. Findings indicate that heterosexual assaults are far more prevalent in Chinese sexual homicides. Sexual murderers who averagely aged 32.44 years are mostly males (97%), single (67%), secondary school educated (68%), and with no prior overall (80%) and sexual (88%) convictions. The victims are mostly females (83%) with mean age of 35.35 years. The frequently observed offending patterns include strangers as victim choice (63%), con tactics as victim approach method (57%), sexual pleasure as primary motivation (49%), and personal weapons as murder weapon of choice (41%). Vaginal penetration is a commonly observed sexual assault (88%) and victim body mutilation is also not uncommon (47%). Three case examples are also presented to illustrate the diverse nature and offending patterns of Chinese sexual homicide offenders.